Diskriminasi Faktor Sebagai Pembeda Kualitas Capital Adecuacy Ratio Bank Perkreditan Rakyat di Yogyakarta - Gendro Wiyono (Jurnal Bisnis dan Ekonomi, 2018)
The purpose of this study to determine the effect of financial ratios differently to the capital adequacy of Rural Banks in the Special Region of Yogyakarta. The number of BPRs 54 is chosen entirely as a sample. Data analysis using discriminant analysis with simultancous estimation method. The results showed that simultaneously seven independent variables can be used to differentiate the level of capital adequacy ratio of Rural Banks. However, partially only 2 (two) independent variables significantly differentiate the level of capital adequacy of banks namely: EQTL and BOPO. The discriminant model formed is useful to predict the BPR CAR position, so that management can more effectively manage capital adequacy to anticipate changes in the BPR business environment.